Assessment of formal tobacco treatment and smoking cessation in dual users of cigarettes and e-cigarettes. Issue 3 (20th July 2022) - Heiden, Brendan T; Baker, Timothy B; Smock, Nina; Pham, Giang; Chen, Jingling; Bierut, Laura J; Chen, Li-Shiun
Abstract : Background: The utility of electronic cigarettes ('e-cigarettes') as a smoking cessation adjunct remains unclear. Similarly, it is unclear if formal tobacco treatment (pharmacotherapy and/or behavioural support) augments smoking cessation in individuals who use both cigarettes and e-cigarettes. Methods: We performed a longitudinal cohort study of adult outpatients evaluated in our tertiary care medical centre (6/2018–6/2020). E-cigarette use, smoking status and formal tobacco treatment (deterrent pharmacotherapy and/or behavioural support) were assessed in 6-month blocks (eg, cohort 1 (C1)=6/2018–12/2018, C2=1/2019–6/2019 and so on) using our electronic health record. We assessed the relationship between e-cigarette use (either with or without formal tobacco treatment) and point prevalence of smoking cessation at 6 and 12 months. Results: 111 823 unique patients were included in the study. The prevalence of dual use of cigarettes and e-cigarettes increased significantly over the study period (C1=0.8%; C2=1.1%; C3=1.8%; C4=2.3%; p<0.001). The prevalence of smoking cessation at 12 months was higher among e-cigarette users (20.8%) compared with non-users (16.8%) (risk difference, 4.0% (95% CI 2.5% to 5.5%); adjusted relative risk (aRR) 1.354, 95% CI 1.252 to 1.464, p<0.0001). Further, among dual users of cigarettes and e-cigarettes, the prevalence of smoking cessation at 12 months was higher among individuals who received tobacco treatment (29.1%) compared with individuals who did not receive tobacco treatment (19.6%) (risk difference, 9.5% (95% CI, 4.6% to 14.4%); aRR 1.238, 95% CI 1.071 to 1.432, p=0.004). Interpretation: These results suggest that dual users of cigarettes and e-cigarettes benefit from formal tobacco treatment. Clinicians should consider offering formal tobacco treatment to such patients, though future trials are needed.